Covid-19: temporal evolution and immunization in the three epidemiological waves, Brazil, 2020-2022 - Erly Catarina Moura; Juan Cortez-Escalante; Fabrício Vieira Cavalcante; Ivana Cristina de Holanda Cunha Barreto; Mauro Niskier Sanchez; Leonor Maria Pacheco Santos (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE Describe the temporal evolution of morbimortality due to Covid-19 and vaccination coverage during the health emergency in Brazil. METHODS Number of cases and deaths due to Covid-19 were extracted from the public panel of the Brazilian Ministry of Health, according to epidemiological week (EW) and geographic region. Data on vaccines and variants were obtained, respectively, from the Information System of the National Immunization Program and the Genomic Surveillance System of SARS-CoV-2. RESULTS Three peaks of deaths characterized the evolution of the Covid-19 pandemic: in EW 30 of 2020, in the EW 14 of 2021 and in the EW six of 2022; three case waves, starting in the North and Northeast regions, with higher rates in the third wave, mainly in the South region. Vaccination started in the epidemiological week three of 2021, rapidly reaching most of the population, particularly in the Southeast and South regions, coinciding with a reduction exclusively in the mortality rate in the third wave. Only from the beginning of the second wave, when Gama was the dominant variant, 146,718 genomes were sequenced. From the last EW of 2021, with vaccination coverage already approaching 70%, the Omicron variant caused an avalanche of cases, but with fewer deaths. CONCLUSIONS We noticed the presence of three waves of Covid-19, as well as the effect of immunization on the reduction of mortality in the second and third waves, attributed to the Delta and Omicron variants, respectively. However, the reduction of morbidity, which peaked in the third wave during the domination of the Omicron variant, remained the same. The national and centralized command of the pandemic confrontation did not occur; thus, public administrators took the lead in their territories. The overwhelming effect of the pandemic could have been minimized, if there had been a coordinated participation of three spheres of the Brazilian Unified Health System administration, in the joint governance of the pandemic fight.